Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-50471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Suction and Injection Purge-Flow on the Secondary Flow Structures of a High-Work Turbine

Abstract: In high-pressure turbines, a small amount of air is ejected at the hub rim seal, to cool and prevent the ingestion of hot gases into the cavity between the stator and the disk. This paper presents an experimental study of the flow mechanisms that are associated with injection through the hub rim seal at the rotor inlet. Two different injection rates are investigated: nominal sucking of −0.1% of the main massflow and nominal blowing of 0.9%. This investigation is executed on a one-and-1/2-stage axial turbine. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…The result showed that the tangential difference of the mainstream and cooling flow was the main reason for flow loss, and pre-swirling was helpful to reduce the negative effect. Similar results were also found by Schuepbach et al 17 and Cui and Tucker. 18 Numerical simulation of Andreini et al 19 indicated that the cooling flow decreased the tangential speed of the mainstream, which consequently reduced the incidence angle of the downstream rotor near the turbine hub wall.…”
Section: Introductionsupporting
confidence: 91%
“…The result showed that the tangential difference of the mainstream and cooling flow was the main reason for flow loss, and pre-swirling was helpful to reduce the negative effect. Similar results were also found by Schuepbach et al 17 and Cui and Tucker. 18 Numerical simulation of Andreini et al 19 indicated that the cooling flow decreased the tangential speed of the mainstream, which consequently reduced the incidence angle of the downstream rotor near the turbine hub wall.…”
Section: Introductionsupporting
confidence: 91%
“…7 They determined that the hub secondary flo ws have a larger radial exten t if the seal air mass flow is increase fro m 0.14% MF to 0.9%MF. In addition the total-to-total efficiency drops by 0.6% if the seal air mass flow is increased.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness, and hence mixing, in the rim seal region was shown to be principally dependent on the sealing mass flow rate, regardless of the seal configuration used inboard to protect the wheelspace. Schuepbach et al 13 conducted an experimental study to show the flow mechanisms that were caused by injection through the rim seal. The injection caused the turbine efficiency to deteriorate by about 0.6%.…”
Section: Introductionmentioning
confidence: 99%
“…Schuepbach et al. 13 conducted an experimental study to show the flow mechanisms that were caused by injection through the rim seal. The injection caused the turbine efficiency to deteriorate by about 0.6%.…”
Section: Introductionmentioning
confidence: 99%